Structural design of a passive wearable exoskeleton to assist oil palm harvesting operation - Mohamad, Muhammad Fuad; Sowat, Sharence Nai; Selamat, Hazlina; Azaman, Aizreena; Harith, Hazreen H. (Malaysian Palm Oil Board, 2022)
Harvesting of oil palm fresh fruit bunches is still performed manually, involving extensive energy, awkward postures or repetitive motion, and often under strenuous conditions. Exoskeleton technologies are increasingly being explored for performance augmentation and ergonomics intervention in industrial settings. For challenging environments, like the oil palm plantation, the dynamic interactions between user, task and environment is non-trivial. Importantly, an exoskeleton should not impede a worker’s movement and task performance throughout the period of wear. Intrinsically, designing an exoskeleton for oil palm harvesting entails that the dynamic interactions between the harvester, the pole, and surrounding objects is considered early in the design process. We adopted the systems approach to designing an upper limb exoskeleton to assist oil palm harvesters. The proposed design is a slimline passive exoskeleton that provides an assistive force through compression springs in the upper arm region. Structural analysis and a preliminary prototype evaluation were performed for design verification. The weakest component was the back plate. Nevertheless, permanent deformation would only occur when an equivalent of 26 kg load is applied to the exoskeleton arm.Future work includes optimising the design and elucidating its long-term effects on the harvester’s efficiency and field productivity through biomechanical analysis and field tests.